What is More Important on Gcg and Financial Performance: The Independent Commissioner or Affiliated Commissioner? Evidence from Indonesian Banks - Jerry Marmen Simanjuntak; Airlangga Surya Kusuma (Celebes Scholar pg, 2025)
Traditionally, an independent Board of Commissioners (BoC) has been considered one of the most important pillars of Good Corporate Governance (GCG). However, unlike agency theory, stewardship theory proposes that BoCs originate from internal companies, and not from outsiders. Thus, this study aims to investigate the comparative importance of affiliated commissioners versus independent commissioners in moderating the relationship between GCG and financial performance in Indonesian banks. Using a sample of 37 Indonesian banks over a ten-year period (2013-2022), the research employed moderated regression analysis to examine these relationships while controlling for various bank-specific characteristics. The study confirms a significant positive relationship between GCG implementation and bank financial performance, as measured by Return on Assets (ROA). The most significant finding of this study relates to the moderating effects of board composition. When control variables are included in the analysis, both independent commissioners and affiliated commissioners demonstrate significant moderating effects on the GCG-performance relationship. However, several important nuances emerge: Independent commissioners show a slightly stronger moderating effect (-2.82455) than affiliated commissioners (-2.613125), suggesting that independent oversight provides marginally greater value in enhancing the effectiveness of GCG practices. Both types of commissioners contribute positively to the GCG-performance relationship, indicating that the traditional dichotomy between agency theory and stewardship theory may be overly simplistic in the Indonesian banking context.